PELATIHAN JURNALISTIK DAN LITERASI MEDIA BAGI KOMUNITAS CREW JURNALISTIK MAN 1 GARUT - Subagja, Ropik; Raturahmi, Leadya (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Advances in the dissemination of information technology have opened up wide opportunities for people to access and disseminate information quickly and effectively. It is almost similar to what is done by the MAN 1 Garut journalistic Crew Community or what is referred to as organizational socialization media that disseminates information in the school environment. However, based on the results of observations, there is a problem experienced by the community, namely the lack of skills and understanding in good and correct journalistic practices, such as in terms of news writing techniques with the inverted pyramid concept, then in writing headlines, photojournalistic captions and interview techniques accompanied by media literacy. With these problems, this Community Service aims to help develop students' skills in the field of journalism, especially in terms of writing news so that it can encourage the formation of quality journalistic products and in accordance with the code of ethics in it. The methods used in this training are Preparation, Implementation, Discussion Forum and Evaluation, and in the three sessions are accompanied by a question and answer system between the speaker and the participants. The training, which was attended by 34 members of the Journalistic Crew, brought significant changes in the cognitive aspect. The results of the training show that participants have been able to write news with the concept of an inverted pyramid in accordance with the rules of journalistic language so that there is an increase in skills and understanding from previously limited now become more aware of other journalistic works.